Return to Sport After ACL Reconstruction With a BTB Versus Hamstring Tendon Autograft: A Systematic Review and Meta-analysis. Issue 12 (15th December 2020) - DeFazio, Matthew W.; Curry, Emily J.; Gustin, Michael J.; Sing, David C.; Abdul-Rassoul, Hussein; Ma, Richard; Fu, Freddie; Li, Xinning
Background: Anterior cruciate ligament (ACL) tears are debilitating injuries frequently suffered by athletes. ACL reconstruction is indicated to restore knee stability and allow patients to return to prior levels of athletic performance. While existing literature suggests that patient-reported outcomes are similar between bone–patellar tendon–bone (BTB) and hamstring tendon (HT) autografts, there is less information comparing return-to-sport (RTS) rates between the 2 graft types. Purpose: To compare RTS rates among athletes undergoing primary ACL reconstruction using a BTB versus HT autograft. Study Design: Systematic review; Level of evidence, 4. Methods: The MEDLINE, Embase, and Cochrane Library databases were searched, and studies that reported on RTS after primary ACL reconstruction using a BTB or HT autograft were included. Studies that utilized ACL repair techniques, quadriceps tendon autografts, graft augmentation, double-bundle autografts, allografts, or revision ACL reconstruction were excluded. RTS information was extracted and analyzed from all included studies. Results: Included in the review were 20 articles investigating a total of 2348 athletes. The overall RTS rate in our cohort was 73.2%, with 48.9% returning to preinjury levels of performance and a rerupture rate of 2.4%. The overall RTS rate in patients after primary ACL reconstruction with a BTB autograft was 81.0%, with 50.0% of athletes returning to preinjury levels of performance and a rerupture rate of 2.2%. Patients after primary ACL reconstruction with an HT autograft had an overall RTS rate of 70.6%, with 48.5% of athletes returning to preinjury levels of performance and a rerupture rate of 2.5%. Conclusion: ACL reconstruction using BTB autografts demonstrated higher overall RTS rates when compared with HT autografts. However, BTB and HT autografts had similar rates of return to preinjury levels of performance and rerupture rates. Less than half of the athletes were able to return to preinjury sport levels after ACL reconstruction with either an HT or BTB autograft.